Inclusive Consumption Immigrants'Access to and Use of Public and Private Goods and Services - Anita Borch (Scandinavian University Press (Universitetsforlaget), 2019)
Consumption plays a powerful role in the social and economic integration of immigrants. Most research on integration has addressed integration through work. Inclusive Consumption adopts a different approach, exploring the inclusive and exclusive potentials of markets and consumption. The book's chapters cover consumption of food, shelter, clothes, mobile phones, leisure activities, employment agency services, physiotherapy education and health services. The key institutions of the welfare society - private and public markets, work, education, and health - are thereby addressed. The book is aimed at students, researchers and professionals with an interest in broader perspectives on social integration of immigrants. The book's contributors are drawn from a variety of disciplines: sociology, social anthropology, ethnology, political science, media studies, journalism, social and rural development, social work, nursing, physiotherapy and textile engineering. With this edited collection, the editors and authors hope to expand the horizons of the debate on social integration of immigrants beyond the prevailing focus on the role of work. An inclusive and open definition of the factors relevant for integration will broaden and enrich the production of knowledge, the development of policy instruments and the public understanding of one of our greatest contemporary challenges.